2019
DOI: 10.1016/s2665-9913(19)30042-6
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-based stratification of patients with primary Sjögren's syndrome: multi-dimensional characterisation of international observational cohorts and reanalyses of randomised clinical trials

Abstract: Background Heterogeneity is a major obstacle to developing effective treatments for patients with primary Sjögren's syndrome. We aimed to develop a robust method for stratification, exploiting heterogeneity in patient-reported symptoms, and to relate these differences to pathobiology and therapeutic response. MethodsWe did hierarchical cluster analysis using five common symptoms associated with primary Sjögren's syndrome (pain, fatigue, dryness, anxiety, and depression), followed by multinomial logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 29 publications
3
59
1
4
Order By: Relevance
“…In another observational study of 2 European cohorts of patients with primary SS, fatigue was observed to decrease as systemic IFN activity increased (24). In a third large observational study from the UK, conducted in 608 patients with primary SS, patients with the lowest symptom burden had the highest expression of IFN‐inducible genes (25). In a recent clinical study of hydroxychloroquine for the treatment of primary SS, it was observed that hydroxychloroquine treatment resulted in a significant decrease in IFN‐inducible gene expression, but no clinical improvement (26).…”
Section: Discussionmentioning
confidence: 99%
“…In another observational study of 2 European cohorts of patients with primary SS, fatigue was observed to decrease as systemic IFN activity increased (24). In a third large observational study from the UK, conducted in 608 patients with primary SS, patients with the lowest symptom burden had the highest expression of IFN‐inducible genes (25). In a recent clinical study of hydroxychloroquine for the treatment of primary SS, it was observed that hydroxychloroquine treatment resulted in a significant decrease in IFN‐inducible gene expression, but no clinical improvement (26).…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies in subgrouping patients with pSS can be applied. A recent study defined four different subgroups based on patient-reported outcome measures of levels of pain, dryness, fatigue, depression and anxiety [ 6 ]. The subgroups differed in laboratory parameters and gene expression as well as response in clinical trials in retrospective analysis of pain, dryness and fatigue scores, and salivary flow measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Given the heterogeneity in clinical presentation of what is currently referred to as pSS, selecting patients and evaluating outcomes in clinical trials has proven difficult. A recent study suggested patient-reported outcome measures to classify patients with pSS into different subtypes [ 6 ]. Variation in clinical manifestations or outcome based on presence or absence of particular biomarkers has also been highlighted [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to have appropriate age distributions, datasets that did not include individuals older than 75 years old or had narrow age distributions were also discarded. A total of five datasets listed in Table 1 were therefore included in the analysis ( Beutner et al, 2011 ; Sood et al, 2015 ; Wingo and Gibson, 2015 ; Peters et al, 2015 ; Tarn et al, 2019 ). Age ranges are large for all datasets, and one dataset (UKPSSR) is composed of almost exclusively female samples ( Appendix 1 Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%